Seasonal variations and the influence of COVID-19 pandemic on hemoglobin A1c, glycoalbumin, and low-density lipoprotein cholesterol - Takebayashi, Kohzo; Yamauchi, Mototaka; Hara, Kenji; Tsuchiya, Takafumi; Hashimoto, Koshi (Diabetology international, 2022)
Aim The purpose of the study was to investigate seasonal variations in HbA1c, GA and LDL-C and to examine the effects of the COVID-19 pandemic on these variations and on glycemic and lipid control themselves in patients with type 2 diabetes. Patients and methods The subjects were outpatients with type 2 diabetes who had received standard treatment for glycemic control for more than 3 years. Data for patients who visited our hospital from January 2021 to March 2021 were retrospectively investigated based on electronic medical records. Results HbA1c showed seasonal variation (high in winter–spring and low in summer–autumn), and this was similar during the COVID-19 pandemic. However, the mean HbA1c over 1 year was significantly elevated during the COVID-19 pandemic (7.53 ± 1.02% in 2020) compared with the previous 2 years: (7.34 ± 0.91 in 2018, 7.39 ± 0.93 in 2019; 2020 vs. 2018; 0.19%, P < 0.001; 2020 vs. 2019; 0.14%, P = 0.0013) and the difference was larger in winter. GA showed no apparent seasonal variation, but mean GA during the COVID-19 pandemic was elevated compared with earlier years (2020 vs. 2018, P < 0.001; 2020 vs. 2019, P < 0.001). LDL-C did not show apparent seasonal variation and was unaffected by COVID-19 pandemic. Conclusion The COVID-19 pandemic influenced mean HbA1c and GA levels over 1 year, but did not affect seasonal variations, while LDL-C was not affected by COVID-19. Observation of these levels over a longer period is warranted to determine the longer-term influence of the COVID-19 pandemic.